The Relationship Between Science Teachers' Career Expectations and Different Professional Development Experiences - Peer S. Daugbjerg; Martin K. Sillasen (European Teacher Education Network, 2016)
The relation between teachers' experience, foreground and the intentions of professional development programs (PDP) has been investigated in a Danish case, where a balance between top-down and bottom-up processes intended to integrate local and individual perspectives of the participating teachers in the overall program. We combine data regarding the teachers' participation in collaborative elements in the PDP and the teachers' individual reflections on their relation to these elements in their personal career foregrounds. Three different participation trajectories were found: - Increasingly convergent entangling trajectory - Mutually enriching but distinctly parallel personal and systemic trajectory - Open-ended trajectory, that keeps different career options open.